2018
DOI: 10.2147/ceor.s167499
|View full text |Cite
|
Sign up to set email alerts
|

The role of a best practice alert in the electronic medical record in reducing repetitive lab tests

Abstract: BackgroundThe recommendations of the American Board of Internal Medicine Foundation’s “Choosing Wisely®” initiative recognize the importance of improving the appropriateness of testing behavior and reducing the number of duplicate laboratory tests.ObjectiveTo assess the effectiveness of an electronic medical record Best Practice Alert (BPA or “pop up”) intervention aimed at reducing duplicate laboratory tests and hospital costs.DesignComparison of the number of duplicated laboratory tests performed on inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…An overview of the characteristics of the included studies is listed in Table 2. Generally, twenty-two studies (81%) [5,[13][14][15][16]18,[20][21][22][23][24][25][28][29][30][31]32,[34][35][36][37][38] out of the included twenty-seven studies report cost savings after implementing an EHR based CDS intervention. Four studies (15%) [17,26,27,33] report a rise in cost expenditure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An overview of the characteristics of the included studies is listed in Table 2. Generally, twenty-two studies (81%) [5,[13][14][15][16]18,[20][21][22][23][24][25][28][29][30][31]32,[34][35][36][37][38] out of the included twenty-seven studies report cost savings after implementing an EHR based CDS intervention. Four studies (15%) [17,26,27,33] report a rise in cost expenditure.…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of included studies the main cost outcome measures were related to laboratory test cost. [15][16][17]20,21,25,28,29,31,32,38] Exploration of different front-end CDS intervention categories According to the taxonomy by Wright et al [12], we identi ed ten (37%) studies [5,13,15,20,22,23,26,[36][37][38] which explored EHR based CDS interventions based on point-of-care alerts or reminders (category 3). Three interventions (11%) [17,27,34] were order facilitators (category 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While our finding contradicts other studies that found that EHR interventions modified provider behavior, this may be explained by some differences specific to our intervention. [15][16][17] It is likely that the EHR intervention here was not robust enough. Instead of ordering vitamin D test using the quick order screen, providers still had the option to order the test using a customized "favorites" screen, "powerplan" screens designed for specific conditions, or 16 (7.4% and 2.4%) while our IM pre-and postintervention rates are higher (9.88% and 7.98% posteducation memo).…”
Section: Discussionmentioning
confidence: 99%
“…14 In previous studies, various combinations of behavioral modification tools including provider education, electronic health record (EHR) based interventions (eg, clinical decision support, alerting), choice architecture modifications (eg, removal from ordering lists), and peer comparison reports have each been applied to help modify providers' ordering behaviors. [15][16][17][18][19][20] In prepost cross-sectional descriptive analyses, Felcher et al 16 found that vitamin D screening rates decreased nearly 70% after implementation of a bundle of 3 clinical decision support tools: educating providers about new screening guidelines, a hard-stop alert (ie, order prevented, justification required to override), and laboratory order list modifications. The authors, however, could not isolate the effect of the education intervention from EHR components.…”
Section: Introductionmentioning
confidence: 99%